A case report of gastrointestinal stromal tumor located in the jejunum - Anas, Belhaj; Terrab, Fatima Zahrae; Tenkorang, Somuah; Ibn Majdoub, Karim; Toughrai, İmane and Farih, Moulay Hassan and Hassouni, Khalid and Mazaz, Khalid (Journal of Surgery and Medicine, 2018)
Among rare primary mesenchymal tumors in the digestive tract are gastrointestinal stromal tumors which are often located in the stomach. This tumor is rarely found in the jejunum with an incidence of 20 to 30% of cases. We report the case of a gastrointestinal stromal tumor of the jejunum in a 67-year-old diabetic patient undergoing treatment.